The Effect Of Show And Tell Method On Students’ Speaking Ability At Eighth Grade Of Mts Diniyah Pandai Sikek - Aulia Sri Wulandari; Genta Sakti; Veni Roza; Irwandi (CV. ULIL ALBAB CORP, 2022)
The purpose of this research was to find out the effect of using Show and Tell method on students’ speaking ability for the eighth-grade students of MTs Diniyah Pandai Sikek. This research was experimental and was conducted in MTs Diniyah Pandai Sikek of Eighth Grade during the 2021/2022 Academic Years. There were two classes: experimental class and control class, in which each class consists of 23 students. The total population was 69 students. This research used purposive sampling. The researchers use an experimental quantitative method for collecting the data. Based on the statement above, the researchers take the whole of two classes or 46 students as a sample. The instrument in collecting the data was an oral test: namely by asking the students to present the information about themselves and asking them one by one to describe their object while the researcher listen to them. Technique of collecting the data by comparing the result of pre-test and post-test both of the classes. Helped by the English teacher, then the scores were classified based on components of speaking, they were vocabulary, pronunciation, grammar, fluency, and comprehension. The result shows that test of t-obtained > t-table or 5.369 > 1.960. It means the hypothesis that there was a significant effect of the Show and Tell method on students’ speaking ability in junior high school.